KONTRIBUSI WANITA TANI TERHADAP PENDAPATAN USAHATANI KARET DI DESA SUGIRAYA KECAMATAN BABAT TOMAN KABUPATEN MUSI BANYUASIN - Gusti Fitriyana (Universitas Tridinanti Palembang, 2018)
This study aims to determine the time allocation used by female farmers to tap rubber and calculate the contribution of women's income to rubber farming income. The method used in this study is a survey method with women working on rubber farming as a sample. Based on the results of the study it was concluded that, 1) The time allocation used by female farmers to tap rubber in Sugiraya Village, BabatTomanSubdistrict was 131.04 hours per month and 3.86 hours per day, while for Non-Farming activities the clothes trade was 26.59 hours per month and for non-economic time is 562.36 hours per month, the time allocation for male farmers used to tap rubber is 131 hours per month, and non-farming time is 589.15 hours per month. 2) The contribution of female farmers to rubber farming income is equal to Rp.2,462,601.35 per cultivated area per month with 50.02 percent of total rubber farming income of Rp.8,890,560.8 per month in Sugiraya Village, BabatToman District, Musi Banyuasin Regency.